Characteristics associated with suppression of spermatogenesis in a male hormonal contraceptive trial using testosterone and Nestorone® gels. (30th September 2013) - Roth, M. Y.; Ilani, N.; Wang, C.; Page, S. T.; Bremner, W. J.; Swerdloff, R. S.; Dart, C.; Sitruk‐Ware, R.; Kumar, N.; Blithe, D.; Amory, J. K.
Summary: Development of a male hormonal contraceptive has been challenging ascribable to the failure to adequately suppress spermatogenesis in 5–10% of men. Methods to identify incomplete suppressors early in treatment might identify men most responsive to male hormonal contraceptives. We hypothesized that serum hormone and gonadotropin concentrations after 4 weeks of transdermal treatment with testosterone and Nestorone in a contraceptive trial would be associated with suppression of sperm concentrations to <1 million/mL after 24 weeks. Indeed, luteinizing hormone or follicle‐stimulating hormone concentrations greater than 1 IU/L after 4 weeks of transdermal testosterone/nestorone treatment were 97% sensitive for predicting failure to suppress spermatogenesis after 24 weeks of treatment. Serum nestorone concentrations were significantly associated with suppression, but serum testosterone concentrations were not. Early suppression of gonadotropins is associated with, but does not ensure, adequate suppression of spermatogenesis. This information may allow for rapid identification of non‐responders in male hormonal contraceptive trials.